Expresidente Óscar Arias Sánchez: retórica del miedo en una Súplica a la Virgen de los Ángeles - Campos Vargas, Henry (2013)
In this paper, it is analized the presidential speech Súplica a la Virgen de los Ángeles from a rhetoric point of view and thepresence of fear as an argument.